Towards molecular simulations of glycans, glycoproteins, and membrane-membrane interactions - Jefferys, V (2021)
Close apposition of membranes is a frequent occurrence in biological systems,and one of considerable physiological and pathological significance. The geo-metric and compositional complexity of such associations, and in some casestheir transient and/or rare occurrence, makes them challenging to study ex-perimentally, and necessitates a multidisciplinary approach to their investiga-tion. Molecular dynamics (MD) simulations have considerable potential toform part of the toolkit for studying membrane interactions, being able to pro-vide molecular-level insight into the time-dependent behaviour of biologicalsystems. However, there at present is no standard approach to prepare and sim-ulate membrane-membrane interactions for MD simulations. In this work, Ipresent progress towards the development of methods that could prove valuablein preparing simulation systems for this purpose.